Plasma Homocysteine Is a Predictive Factor for Accelerated Renal Function Decline and Chronic Kidney Disease in a Community-Dwelling Population - Wenkai Xiao; Ping Ye; Fan Wang; Ruihua Cao; Yongyi Bai; Xiaona Wang (Karger Publishers, 2021)
Background: Whether elevated plasma total homocysteine (tHcy) is a risk factor for the progression of kidney disease in general population has not been well established. The purpose of this study was to investigate the prognostic properties of plasma tHcy for renal function decrement and early chronic kidney disease (CKD) in community-dwelling populations with normal renal function at baseline. Methods: A total of 1,426 participants were enrolled and followed for a median of 4.8 years (interquartile range, 4.5-5.2), and estimated glomerular filtration rate (eGFR) was evaluated. One main outcome was the rapid eGFR decline defined as a decline in eGFR of >3 mL/min per 1.73 m2 per year; the other was the new incidence of CKD. Results: At the end of follow-up, the incidence of rapid eGFR decline and new-onset CKD was 20.7 and 5.6%, respectively. In multivariate linear regression analysis, age, central pulse pressure, fasting blood glucose, and concentration of tHcy were independent determinants of the change in eGFR. There was a graded association between tHcy quartiles and eGFR decline. Compared with participants with the lowest quartile of tHcy levels, those with the highest quartile had significantly increased risk for rapid eGFR decline (adjusted odds ratio [aOR] = 1.81; 95% confidence interval [CI]: 1.25-2.94) and new onset of CKD (adjusted hazard ratio = 4.29; 95% CI: 1.42-12.99) after adjusting for various confounders. Similarly, significant associations were also found when baseline tHcy was classified as hyperhomocysteinemia (>15 μmol/L) versus normal tHcy level (≤15 μmol/L). However, there was only association between the change in tHcy levels and new occurrence of CKD but not with rapid eGFR decline (aOR = 0.99, p = 0.613). Conclusions: In this prospective cohort of individuals from community-based population, elevated plasma tHcy emerged as an independent predictor of renal function decline and incident CKD, which might support selection of at-risk individuals.